60th birthday of Mykola Korynevskii (Condensed Matter Physics, 2007)
On January 18, 2008 member of the Editorial
Board of “Condensed Matter Physics”,
Leading Researcher of the Institute for Condensed
Matter Physics, Doctor of Sciences in
physics and mathematics Mykola Korynevskii
celebrates his 60th birthday.